Pooled Subject-Reported Outcomes From 2 Phase 3 Studies of OnabotulinumtoxinA for Simultaneous Treatment of Forehead and Glabellar Lines. Issue 7 (July 2020) - Ogilvie, Patricia; Rivkin, Alexander Z.; Dayan, Steven; Yoelin, Steven G.; Larsen, Kristin E.; Varon, Sepideh; Garcia, Julie K.
Abstract : BACKGROUND: Understanding the subjects' perspective is critical for successfully treating upper facial lines. OBJECTIVE: To understand subjects' self-perception and overall satisfaction after onabotulinumtoxinA treatment for forehead and glabellar lines. METHODS: This analysis pooled data from two 12-month, pivotal phase 3 studies in which toxin-naive subjects received onabotulinumtoxinA 40 U or placebo for treatment of upper facial lines. OnabotulinumtoxinA was administered as 0.1-mL injections at 10 prespecified sites (frontalis: 20 U; glabellar complex: 20 U). Each study used 3 reliable and validated patient-reported outcome instruments to evaluate subject satisfaction and appearance-related psychological effects: the Facial Line Satisfaction Questionnaire (FLSQ), the Facial Line Outcomes (FLO-11) Questionnaire, and the Self-Perception of Age (SPA) Questionnaire. In total, data for 865 subjects (608, onabotulinumtoxinA 40 U; 257, placebo) were analyzed. RESULTS: Treatment with onabotulinumtoxinA 40 U resulted in significant and sustained improvements across all pooled FLO-11 items and FLSQ items compared with placebo. SPA results demonstrated that a significant proportion of subjects in the pooled analysis felt they looked younger after treatment than at baseline (all, p < .0001 vs placebo). CONCLUSION: This study demonstrates a high level of treatment satisfaction and significantly improved appearance-related psychological outcomes among toxin-naive subjects after onabotulinumtoxinA 40 U treatment.